2021
DOI: 10.3389/fimmu.2021.582768
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Features of FLAIR-Hyperintense Lesions in Anti-MOG Antibody Associated Cerebral Cortical Encephalitis with Seizures: Case Reports and Literature Review

Abstract: BackgroundThe presence of fluid attenuated inversion recovery (FLAIR)-hyperintense lesions in anti-myelin oligodendrocyte glycoprotein (MOG) antibody-associated cerebral cortical encephalitis with seizures (FLAMCES) was recently reported. However, the clinical characteristics and outcome of this rare clinico-radiographic syndrome remain unclear.MethodsThe present study reported two new cases. In addition, cases in the literature were systematically reviewed to investigate the clinical symptoms, magnetic resona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 21 publications
0
29
0
Order By: Relevance
“…We finally obtained 33 cases from 25 articles and combined with our two cases, a total of 35 cases were reviewed systematically ( Ogawa et al, 2017 ; Hamid et al, 2018 ; Ikeda et al, 2018 ; Budhram et al, 2019 , 2020 ; Haddad et al, 2019 ; Patterson et al, 2019 ; Fujimori et al, 2020b ; Hochmeister et al, 2020 ; Katsuse et al, 2020 ; Matoba et al, 2020 ; Otani et al, 2020 ; Russ et al, 2020 ; Takamatsu et al, 2020 ; Tao et al, 2020 ; Ahsan et al, 2021 ; Chang et al, 2021 ; Doig et al, 2021 ; Jain et al, 2021 ; Kim et al, 2021 ; Maniscalco et al, 2021 ; Nie et al, 2021 ; Stamenova et al, 2021 ; Tian et al, 2021 ; Wang et al, 2021 ; Table 1 ). The main demographic data, clinical characteristics, laboratory results, and imaging results are presented in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We finally obtained 33 cases from 25 articles and combined with our two cases, a total of 35 cases were reviewed systematically ( Ogawa et al, 2017 ; Hamid et al, 2018 ; Ikeda et al, 2018 ; Budhram et al, 2019 , 2020 ; Haddad et al, 2019 ; Patterson et al, 2019 ; Fujimori et al, 2020b ; Hochmeister et al, 2020 ; Katsuse et al, 2020 ; Matoba et al, 2020 ; Otani et al, 2020 ; Russ et al, 2020 ; Takamatsu et al, 2020 ; Tao et al, 2020 ; Ahsan et al, 2021 ; Chang et al, 2021 ; Doig et al, 2021 ; Jain et al, 2021 ; Kim et al, 2021 ; Maniscalco et al, 2021 ; Nie et al, 2021 ; Stamenova et al, 2021 ; Tian et al, 2021 ; Wang et al, 2021 ; Table 1 ). The main demographic data, clinical characteristics, laboratory results, and imaging results are presented in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Since MOG antibody (MOG-Ab)-related cerebral cortical encephalitis (CCE) was first reported by Ogawa et al (2017) , many cases of this rare clinical phenotype have been reported globally, which may have been diagnosed with unexplained steroid-responsive encephalitis in the early stages of the disease ( Wang et al, 2021 ). CCE is a syndrome with an unclear clinical definition and is characterised by grey matter lesions on brain MRI, primarily involving the cerebral cortex and sulcus, but not the subcortical and deep white matter ( Krupp et al, 2013 ; Ogawa et al, 2017 ; Hamid et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…FLAMCES is a recently reported subtype of MOGAD that is mainly characterized by hyperintense lesions on MRI FLAIR sequences, cortical encephalitis, and seizures. Approximately 21 cases have now been reported ( Budhram et al, 2019 ; Mirian et al, 2021 ; Wang et al, 2021 ). According to Wang’s review, the age of onset was younger (26.8 years on average), with a larger proportion of males (76.2%).…”
Section: Othermentioning
confidence: 99%
“…All the patients received glucocorticoid therapy and showed recovery of symptoms and lesions. Some patients (9/21) were treated with antiepileptic drugs, and no unprovoked seizures were reported ( Wang et al, 2021 ). Because seizures are thought to be caused by encephalitis, long-term antiepileptic drugs are not recommended.…”
Section: Othermentioning
confidence: 99%
“…Myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD) is an inflammatory demyelinating disease of the central nervous system (CNS), and typically presents as optic neuritis, transverse myelitis, brainstem demyelination and acute disseminated encephalomyelitis (1). Recently, MOG antibody-related cerebral cortical encephalitis, a rare clinical phenotype of MOGAD, has been reported (2,3). Of note, atypical clinical manifestations for demyelinating diseases including fever, seizures, headaches, and cerebral cortical symptoms such as aphasia, mental disorder, and memory impairment, are common in MOG cortical encephalitis (1).…”
Section: Introductionmentioning
confidence: 99%